Sequential detection of multiple phase transitions in model biological membranes using a red-emitting conjugated polyelectrolyte. Issue 18 (21st April 2016) - Houston, Judith E.; Kraft, Mario; Scherf, Ullrich; Evans, Rachel C.
Abstract : Charge-mediated assembly of an anionic poly(thiophene) leads to a highly sensitive probe of membrane order. Abstract : The anionic conjugated polyelectrolyte, poly[3-(6-sulfothioatehexyl)thiophene] (P3Anionic ), functions as a highly sensitive probe of membrane order, uniquely capable of sequentially detecting the three key phase transitions occurring within model phospholipid bilayers. The observed sensitivity is the result of charge-mediated, selective localisation ofP3Anionic within the head-groups of the phospholipid bilayer.